Leadership Strategies for Integrated Service Innovation: The Role of Transformational Leadership and Supervision on Employee Performance - Lulu Kamelia; Asep Jamaludin; Nandang Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Employee performance in government organizations plays a crucial role, particularly in improving public services. This study aims to examine and analyze the influence of transformational leadership on employee performance at the Investment and One-Stop Integrated Services Office of Karawang Regency, with supervision as a moderating variable. The research adopts a quantitative approach with a descriptive-verificative design. It seeks to explain phenomena based on collected data and to test theoretical assumptions against real-world findings. The sample consists of 50 employees of the Karawang Regency Investment and One-Stop Integrated Services Office, selected through a full sampling technique, where the entire population was used as the sample. Data were collected via surveys distributed to employees and then analyzed using Structural Equation Modeling (SEM) with SMART PLS software. The results indicate that transformational leadership significantly affects employee performance. Supervision also plays a crucial role in enhancing performance. Additionally, transformational leadership has a significant influence on supervision. Furthermore, supervision acts as a moderating variable, strengthening the relationship between transformational leadership and employee performance.